2019
DOI: 10.1038/s42255-018-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial regulation of organismal energy homeostasis

Abstract: Facts and figures on the gut microbiota The term microbiota refers to all the microorganisms present in the various ecosystems in the human body. Diverse communities of microorganisms are located throughout the human body, including the gut, lungs, vaginal and urinary tracts and skin. The microbiota is composed of several types of microbes: bacteria, archaea, viruses, phages, yeast and fungi 1. Humans have constantly coevolved in the presence of these microorganisms, thereby establishing symbiotic relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
326
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(338 citation statements)
references
References 213 publications
(252 reference statements)
5
326
0
7
Order By: Relevance
“…In addition, Mills and colleagues demonstrated that succinate accumulates in BAT upon cold exposure and favors thermogenesis in an UCP1-dependent manner [164]. Furthermore, gut microbiota has been described in the past two decades as a very important player in the regulation of whole-body energy homeostasis, in response to diverse stimuli such as cold [165,166], nutrition [167,168], or fasting/feeding cycles [168][169][170], through the production of mediators such as short chain fatty acids (SCFAs) and secondary BAs [167,169].…”
Section: Molecule Situation In Pathophysiological Conditions Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Mills and colleagues demonstrated that succinate accumulates in BAT upon cold exposure and favors thermogenesis in an UCP1-dependent manner [164]. Furthermore, gut microbiota has been described in the past two decades as a very important player in the regulation of whole-body energy homeostasis, in response to diverse stimuli such as cold [165,166], nutrition [167,168], or fasting/feeding cycles [168][169][170], through the production of mediators such as short chain fatty acids (SCFAs) and secondary BAs [167,169].…”
Section: Molecule Situation In Pathophysiological Conditions Referencesmentioning
confidence: 99%
“…Furthermore, gut microbiota has been described in the past two decades as a very important player in the regulation of whole‐body energy homeostasis, in response to diverse stimuli such as cold , nutrition , or fasting/feeding cycles , through the production of mediators such as short chain fatty acids (SCFAs) and secondary BAs .…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota is composed of trillions of microorganisms inhabiting the intestines. In recent years, the interactions between gut microbes and host have been shown to influence many physiological responses, including energy metabolism, immune maturation, and neurodevelopment in the human body . The imbalance of gut microbiota, known as dysbiosis, has also been revealed to correlate with numerous human disease phenotypes .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the interactions between gut microbes and host have been shown to influence many physiological responses, including energy metabolism, immune maturation, and neurodevelopment in the human body. [1][2][3][4] The imbalance of gut microbiota, known as dysbiosis, has also been revealed to correlate with numerous human disease phenotypes. 5,6 Notably, the effects of gut microbiota are only not confined to the intestine but can systemically contribute to human disease and health.…”
Section: Introductionmentioning
confidence: 99%
“…For example, SCFAs induced by fiber-enriched diets play important roles in the microbiotagut-brain communication pathway, through the regulation of appetite, energy homeostasis, and maintenance of the intestinal barrier function(Byrne, Chambers, Morrison, & Frost, 2015;Cani et al, 2019).Interestingly, with the exception of an alteration in gut microbiota composition, different microbial CAZyme gene family profiles and AMPK β levels were observed between the groups. Specifically, two genera, Dubosiella and Bacillus, were significantly more abundant in the RM group, which could contribute to ecological dysbiosis and, consequently, colon inflammation.…”
mentioning
confidence: 99%